Web based medical decision support system application of Coronary Heart Disease diagnosis with Boolean functions minimization method - Basciftci, Fatih; Incekara, Hayri (Expert systems with applications, 2011)
► In this study, Medical Expert System has been done by 9 symptoms of Coroner Heart Diseases (9 symptoms, 2 9 =512 different conditions). ► An accuracy table has been formed with 512 different conditions and simplified with the Boolean functions minimization methods. ► 512 different conditions which have been evaluated are reduced to 94 conditions by the minimization method of Boolean functions. ► Reduced conditions obtained, have formed the realized medical expert system rule base. ► People can find out that they have Coroner Heart Diseases or not, with this ES without going to an expert doctor. Heart and vein diseases are one of the most important health problems. The number of the people who died of heart and vein diseases is more than the number of the people who died of all other health problems and natural disasters. In order to decrease this number, the intervention must be started very earlier and people must be informed about this subject. In this study, Medical Expert System has been used all the probabilities of CHD has been determined (9 symptoms, 2 9 = 512 different occasions) and from these probabilities, an accuracy table has been formed. This accuracy table has been simplified with the Boolean functions simplifying methods. 94 rules have been achieved by the Boolean functions minimization method. The rules achieved have formed the Expert System’s rule base. 303 patients’ values have been compared with the realized Expert System. The Medical Expert System which was formed as a result of the evaluation has evaluated men with 86.5%, women with 84.5% and in general with 86.1% accuracy rate.